Isokinetic quadriceps and hamstring muscle strength values in K League 1 professional soccer players - Song, M.-K. (Korean Journal of Sport Science, 2021)
PURPOSE: This study aimed to present isokinetic quadriceps and hamstring muscle strength values in K league 1 (K1) professional soccer players and compare these results to those of published studies. METHODS: A total of 31 K1 soccer players (age 24.5±4.2) without a history of lower limb injury were included in this study. Isokinetic knee strength tests were implemented at a velocity of 60°·s-1 and 180°·s-1 for both dominant (D) and non-dominant (ND) legs using a dynamometer. Strength variables included peak torque (PT), body mass normalized PT (NPT), bilateral strength difference (BD), and hamstring to quadriceps strength (H/Q) ratio. RESULTS: At 60°·s-1 velocity, the NPTs of the quadriceps were 3.39N·m·kg-1 and 3.33N·m·kg-1 for D and ND legs, respectively, and those of the hamstrings were 2.00N·m·kg-1 and 1.89N·m·kg-1 for D and ND legs, respectively. At 180°·s-1 velocity, the NPTs of the quadriceps were 2.31N·m·kg-1, 2.27N·m·kg-1 for D and ND legs, respectively, and those of the hamstrings were 1.42N·m·kg-1, 1.39N·m·kg-1 for D and ND legs, respectively. At all velocities, the BDs of quadriceps and hamstring muscles ranged from 6.6-7.8%, and H/Qs ranged from 57-62%. Compared to previous studies that did not consider the history of injury, this study showed lower levels of BD (less than 10%) and higher levels of NPT. CONCLUSIONS: The presented isokinetic quadriceps and hamstring muscle strength values can be used as reference values for the isokinetic knee strength of K1 professional soccer players.